2015
DOI: 10.1038/srep09524
|View full text |Cite
|
Sign up to set email alerts
|

Classification of foodborne pathogens using near infrared (NIR) laser scatter imaging system with multivariate calibration

Abstract: An optical sensor system, namely NIR laser scatter imaging system, was developed for rapid and noninvasive classification of foodborne pathogens. This developed system was used for images acquisition. The current study is focused on exploring the potential of this system combined with multivariate calibrations in classifying three categories of popular bacteria. Initially, normalization and Zernike moments extraction were performed, and the resultant translation, scale and rotation invariances were applied as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…We used the radial basis function (RBF) kernel as the kernel function of the LS-SVM and the grid-search algorithm to determine the regularization parameter c and the RBF kernel function parameter γ 2 . The optimum parameters are reached when the smallest root-mean-square error (RMSE) is produced 28 .…”
Section: Methodsmentioning
confidence: 99%
“…We used the radial basis function (RBF) kernel as the kernel function of the LS-SVM and the grid-search algorithm to determine the regularization parameter c and the RBF kernel function parameter γ 2 . The optimum parameters are reached when the smallest root-mean-square error (RMSE) is produced 28 .…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, two distinct kinds of spectral variable selection algorithms of RF 19 and SP 20 were conducted to extract the most important spectral wave bands to determine the collision strength index of EVAC. The RF algorithm is a dynamic process of simple random walk, which is considered as similar as the algorithm of reversible jump Markov chain Monte Carlo is implemented in an iterative way.…”
Section: Theory and Approachesmentioning
confidence: 99%
“…The paper is organized as follows: Section 2 describes the materials and devices. Section 3 presents theory and approaches of random frog (RF) 19 , successive projection (SP) 20 , support vector machine regression (SVMR) 21 and performance assessment. Section 4.1 and 4.2 explains the relationship between the absorption attributes of NIR spectroscopy and the inner chemical composition of EVAC materials.…”
mentioning
confidence: 99%
“…Raman spectroscopy has been found to have increasing applications in the field of foodborne pathogen detection due to its rapid and ultrasensitive properties [9,10]. Pan et al reported a near infrared (NIR) laser scattering imaging system for rapid and noninvasive classification of foodborne pathogens [11]. The study results explored the potential of this system combined with multivariate calibrations for classifying three categories of common bacteria.…”
Section: Introductionmentioning
confidence: 99%